Case report: Sleep deprivation presenting as acute psychosis - Sawant, Neena S; Thakurdesai, Abha (Indian Journal of Case Reports, 2018)
Sleeping is a basic human need and plays a key role in good health and well-being. Sleep deficiency can lead to physical and mental health problems, injuries, loss of productivity, and even a greater risk of death. Sleep deprivation is seen in several psychiatric disorders, and there may be a cause or effect relationship. Sleep-deprived individuals may have trouble making decisions, solving problems, controlling their emotions and behavior, and coping with stress or change. We report a case who started having sleep deprivation over 15 days following a stressor, which resulted in an acute psychosis-like condition with associated disorientation and perplexity. However, the patient responded to benzodiazepine medication given for the restoration of her sleep cycle and did not require any antipsychotics. There was also complete amelioration of her behavioral and thought disturbances.